2013
DOI: 10.1590/s1806-83242013005000005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cement-curing mode and light-curing unit on the bond durability of ceramic cemented to dentin

Abstract: The aim of this study was to evaluate the effects of different light-curing units and resin cement curing types on the bond durability of a feldspathic ceramic bonded to dentin. The crowns of 40 human molars were sectioned, exposing the dentin. Forty ceramic blocks of VITA VM7 were produced according to the manufacturer's recommendations. The ceramic surface was etched with 10% hydrofluoric acid / 60s and silanized. The dentin was treated with 37% phosphoric acid / 15s, and the adhesive was applied. The cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…An important aspect of our results is how low all the microtensile values were (2.2-9.7 MPa) when compared to those of other studies (10-30 MPa). 40,[58][59][60][61][62] In addition, it is important to emphasize that the standard deviation values (Table 4) were similar among all groups, suggesting that the results are reliable and that the experiment was well executed. These low values might be related to the polymerization shrinkage stress of the Rely X ARC, which has a negative influence on the bond strength to dentin, resulting in much lower bond strength values, even under ideal geometric situations.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of our results is how low all the microtensile values were (2.2-9.7 MPa) when compared to those of other studies (10-30 MPa). 40,[58][59][60][61][62] In addition, it is important to emphasize that the standard deviation values (Table 4) were similar among all groups, suggesting that the results are reliable and that the experiment was well executed. These low values might be related to the polymerization shrinkage stress of the Rely X ARC, which has a negative influence on the bond strength to dentin, resulting in much lower bond strength values, even under ideal geometric situations.…”
Section: Discussionmentioning
confidence: 99%
“…Chair-side CAD/CAM applications offer many advantages to patients including elimination of laboratory processing costs and the need for temporization of the prepared tooth structure [1]. Durable adhesion between dental tissues and ceramics plays a crucial role in the success of restorations that do not have retentive properties [2][3][4][5][6]. When bonding ceramic restorations to dental substrates, it is crucial to ensure optimal adhesion of resin cement to both the dentin and ceramic surface [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Özcan et al [22], resin materials absorb water during storage over time and a period of days or weeks are required to achieve maximum absorption. Previous studies evaluating the influence of water absorption on bond strength of resin cements to dentine also found that TC was a negative effect for the experimental conditions [9,10,47].…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, the highest bond strength was found in all groups submitted to longer polymerization (V1 80s , V2 80s and V3 80s ), even after TC. Some studies have suggested longer polymerization [47] and high intensity light sources for cementation of thicker ceramic restorations [10] to manage the negative effect of ceramic thickness. This occurs because increasing the time of exposure to light promotes a higher degree of polymerization, and a higher conversion degree of dual resin cement monomers [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation